The Community of the Learned and Seyhulislam in the Early Ottoman State (1300-1566) - Kuspinar, Bilal (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Community of the Learned and Seyhulislam in the Early Ottoman State (1300-1566)